SISTEM INFORMASI KOS DAN KONTRAKAN YOGYAKARTA BERBASIS WEB - , ELIAN GIOVANI, Anindita Suryarasmi, S.kom., M.kom. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
A large number of educational institutions to make Yogyakarta university level with the main purpose of prospective students for college. Both prospective students who come from out of town or from within the city. The prospective student must require a residence or boarding houses and rented. Prospective students who would choose as a boarding house or rented residence requires the right information, accurate and complete information about boarding house / rented house they will occupy. For it was made a information system that manages data and advertisement boarders rented in Yogyakarta area. The system provides information boarding house/rented house from where the information, prices, photos and facilities are all available rooms in this system. It is very easy for students to conduct information searches boarding house/rented house as compared to previous methods. In addition this system also provides facilities for the owners of the boarding / rented to register as a member and advertise in this system. While the level admin system to add features see the data member, see advertising data, see all the testimony, see all the questions and scoring recap monthly advertising data. Implementation of this system making use of the Apache Web server, MySQL database and PHP programming language.